Hypertension screening during healthcare pediatric visits. Issue 5 (May 2015) - Stabouli, Stella; Sideras, Lazaros; Vareta, Georgia; Eustratiadou, Marianna; Printza, Nikoleta; Dotis, John; Kotsis, Vasilios; Papachristou, Fotios
<x xml:space="preserve">Abstract</x> Background: Guidelines in both Europe and the United States recommend screening for hypertension during child care pediatric visits in children above 3 years old. The aims of the study were to assess the frequency of blood pressure (BP) measurement during preventive or chronic care pediatric visits and determine the factors that may associate with screening. Method: We prospectively included in the study consecutive children hospitalized in our department. Anthropometric measurements were performed in all children. Office BP was measured in children above 5 years old and mothers and/or fathers. Personal and family history, and self-reported BP screening during pediatric visits were recorded. Results: Hypertension screening had been performed at least once in 45.3% of the children during pediatric visits. Fifty per cent of the children with elevated BP levels had never been screened for hypertension. Low birth weight, history of prematurity, or chronic disease was not associated with increased frequency of screening, whereas screening was more likely in children above 3 years old with positive personal history (odds ratio 2.35, 95% confidence interval 1.07–5.15, P < 0.05). Obesity tended to increase the frequency of hypertension screening in all ages (odds ratio 2.60, 95% confidence interval 0.93–7.28, P = 0.06). Moreover, 37.5% of children without positive personal history exhibited BP levels above the 90th percentile, and 13.5% of mothers and 31.1% of fathers were not aware of their own elevated BP levels. Conclusion: These findings suggest that hypertension screening does not occur during pediatric visits for a considerable percentage of children, although a significant number of children and adolescents without positive history of hypertension or chronic disease may have elevated office BP levels.